High frequency magnetic fluctuations correlated with the inter-ELM pedestal evolution in ASDEX Upgrade. (17th May 2016) - Laggner, F M; Wolfrum, E; Cavedon, M; Mink, F; Viezzer, E; Dunne, M G; Manz, P; Doerk, H; Birkenmeier, G; Fischer, R; Fietz, S; Maraschek, M; et al.
Abstract: In order to understand the mechanisms that determine the structure of the high confinement mode (H-mode) pedestal, the evolution of the plasma edge electron density and temperature profiles between edge localised modes (ELMs) is investigated. The onset of radial magnetic fluctuations with frequencies above 200 kHz is found to correlate with the stagnation of the electron temperature pedestal gradient. During the presence of these magnetic fluctuations the gradients of the edge electron density and temperature are clamped and stable against the ELM onset. The detected magnetic fluctuation frequency is analysed for a variety of plasma discharges with different electron pressure pedestals. It is shown that the magnetic fluctuation frequency scales with the neoclassically estimated E × B velocity at the plasma edge. This points to a location of the underlying instability in the gradient region. Furthermore, the magnetic signature of these fluctuations indicates a global mode structure with toroidal mode numbers of approximately 10. The fluctuations are also observed on the high field side with significant amplitude, indicating a mode structure that is symmetric on the low field side and high field side. The associated fluctuations in the current on the high field side might be attributed to either a strong peeling part or the presence of non-adiabatic electron response.